PENERAPAN STUDENT TEAM ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN PRESTASI BELAJAR MATEMATIKA SISWA MAN 2 BANYUWANGI - Haridi Haridi (Jurnal Ilmiah Ar-Risalah: Media Ke-Islaman, Pendidikan dan Hukum Islam, 2018)
The purpose of this classroom action research is to know the learning model of Student Team Achievement Division (STAD) can improve student learning achievement MAN Genteng Banyuwangi Class X IPS 2 semester 2 year lesson 2016/2017. This research uses 2 cycles. Use the Kemmis and Taggart research model from one cycle to the next. Data analysis in this study is a qualitative analysis that produces descriptive research results. The results show that; Average learning outcomes followed by mastery of learning. Cycle I reaches an average of 65 and 66.66%. Cycle II reaches an average of 72.3 and 76.92. students complete learning 100%. Learning has reached 100% gain 60-> 60 then the target has been reached. Student Team Achievement Division (STAD) model can improve student learning achievement MAN Genteng Banyuwangi Class X IPS 2 semester 2 Year lesson 2016/2017 "Based on the results of this study it is suggested that teachers in Class Action Research (PTK) know problems in the learning process for improve the quality of education so that students' learning achievement can be increased For researchers interested in applying STAD type cooperative learning should pay attention to the material in accordance with this learning, and should prepare well for the learning process to run smoothly.